The possible effect on frequency of cycling if mandatory bicycle helmet legislation was repealed in Sydney, Australia: a cross sectional survey. - Rissel, Chris; Li Ming Wen (Australian Health Promotion Association, 2011)
A cross sectional survey by a market research company was conducted, using quota sampling, in Sydney, Australia. Participants were 600 residents aged 16 years and older. Data were collected in October 2010 using computer-assisted telephone interviews from randomly sampled households, with one respondent per household. The primary outcome measures were propensity to cycle more if a helmet was not required, how often a respondent who cycled would cycle without a helmet, and opinion on compulsory wearing of bicycle helmets. Frequency of cycling, and demographic questions were also assessed. Multiple logistic regression models were run for each of the three main outcomes. While a hypothetical situation, if only half of the 22.6% of respondents who said they would cycle more if they did not have to wear a helmet did ride more, Sydney targets for increasing cycling would be achieved by repealing mandatory bicycle helmet legislation. A significant proportion of the population would continue to wear helmets even if they were not required to do so.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Erhebung; Studie; Fahrradhelm; Helmpflicht; Fahrradförderung; Radverkehrsförderung